2018
DOI: 10.1038/s41388-017-0077-z
|View full text |Cite|
|
Sign up to set email alerts
|

Wild-type and mutated IDH1/2 enzymes and therapy responses

Abstract: Isocitrate dehydrogenase 1 and 2 (IDH1/2) are key enzymes in cellular metabolism, epigenetic regulation, redox states, and DNA repair. IDH1/2 mutations are causal in the development and/or progression of various types of cancer due to supraphysiological production of d-2-hydroxyglutarate. In various tumor types, IDH1/2-mutated cancers predict for improved responses to treatment with irradiation or chemotherapy. The present review discusses the molecular basis of the sensitivity of IDH1/2-mutated cancers with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
177
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(183 citation statements)
references
References 98 publications
4
177
0
2
Order By: Relevance
“…Analysis of CPT1-isoform expression revealed increased expression of CPT1A in IDH1 mutant cultures relative to IDH wildtype cells. 13 C-palmitic acid revealed extensive FA utilization throughout the metabolomes of both IDH mutant and WT cells. However, the effects of FAO inhibition with ETOM was more pronounced within the TCA cycle of IDH WT cells.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Analysis of CPT1-isoform expression revealed increased expression of CPT1A in IDH1 mutant cultures relative to IDH wildtype cells. 13 C-palmitic acid revealed extensive FA utilization throughout the metabolomes of both IDH mutant and WT cells. However, the effects of FAO inhibition with ETOM was more pronounced within the TCA cycle of IDH WT cells.…”
Section: Discussionmentioning
confidence: 97%
“…To further determine how and where FAs are utilized within U87 cells, untreated CNTL cells, cells treated with ETOM, and cells with CPT1A knockdown were subjected to LC-MS metabolomic analysis using fully-labeled 13 C palmitic acid in physiological glucose conditions (2.5 mM). Analyzing fractional contribution (or the percent of labeled carbons for each metabolite) within these samples revealed labeling throughout the TCA cycle as well as in the ubiquitously important currency metabolite ATP.…”
Section: Fatty Acid and Ketone Oxidation In U87mentioning
confidence: 99%
See 1 more Smart Citation
“…We curated a list of 100 genes (Supplementary Figure 2A. One of the RT-PCR validated ASE prostate cancer genes is IDH1, a key metabolic gene regulating TET2 mediated epigenetic re-programing in prostate tumor cells 39,40 . We found that casodex treatment of all three prostate cancer cell lines resulted in a switch from ENST00000345146, a dominant transcript of IDH1 to ENST00000415913 with an alternate 5'UTR ( Supplementary Figure 1).…”
Section: Functional Analysis Of Genes Regulated At the Level Of Altermentioning
confidence: 99%
“…By contrast, wildtype IDH1 promotes the metabolic adaptation of GBM cells to support aggressive growth (5). Therefore, it has been proposed that the balance between wild-type and mutant IDH1/2 function determines the clinical outcome of gliomas, including their sensitivity to radiation and chemotherapy (6).…”
Section: Introductionmentioning
confidence: 99%